2 - Contemporary Discourses in Qualitative Research: Lessons for Health Research in Nigeria - Ali A. Abdullahi; Anton Senekal; Cecilia Van Zyl-Schalekamp; Jimoh Amzat; T. Saliman (African Sociological Review, 2013)
Quantitative research has permeated and dominated health research in Nigeria. One of the oldest and the most commonly used quantitative research designs are KAP (knowledge, attitude and practice) surveys. Although KAP surveys are important approaches to assessing distribution of community knowledge in large-scale projects, such surveys are often inundated by challenges, especially with regard to accurate measurement and understanding of social construction of health and illness. This paper examines contemporary ontological, epistemological, axiological and methodological discourses in the qualitative research approach and argues for adequate utilisation of the qualitative approach in health research in Nigeria. The qualitative approach deepens understanding of cultural milieu regarding health beliefs and socio-cultural issues surrounding medical therapy, as well as health seeking behaviour. Therefore, this paper argues for a more participatory research methodology in the understanding of health, illness and disease in Nigeria. Some case studies of qualitative research from Nigeria and abroad were reviewed from which health researchers (clinical managers and health social scientists and public health experts) could learn. The paper is thus a contribution to the ongoing discourses in global qualitative health research.